Teachers’ Financial Literacy, Concerns, and Well-Being: A Basis for Financial Program Design - Zerna, Enrico (Journal of Interdisciplinary Perspectives, 2024)
This descriptive–correlational study aimed to assess and analyze teachers' financial literacy, concerns, and well-being to develop a targeted financial program. The study involved 241 randomly selected teachers from the Division of Siquijor. Data were collected using validated questionnaires, and analysis was performed using percentage distribution, weighted mean, and Spearman Rank Correlation Coefficient. The findings revealed that: a) the teachers' financial literacy, in terms of financial knowledge and capability, was at a moderate level, while their financial skills were at a high level; b) their financial literacy, about financial awareness, concerns, and decisions, was also at a moderate level, though their financial goals were more advanced (high); and c) their financial well-being, particularly in terms of financial security, was at slightly applicable level. Moreover, the study found that a) there is a moderate relationship between teachers’ financial literacy and their financial well-being; b) teachers' financial literacy is significantly related to their financial concerns; and d) although the relationship between teachers' financial awareness and financial well-being is significant, the indicators are too weak to draw a strong conclusion.